Peningkatan pengetahuan Peningkatan Pengetahuan Remaja Melalui Edukasi Pencegahan Infeksi Menular Seksual Pada Remaja: Peningkatan Pengetahuan Remaja Melalui Edukasi Pencegahan Infeksi Menular Seksual - Kartini Massa; Nurul Safira Lahati; Noifke Kaghoo; Mira Kumayas (Progran Studi Farmasi Universitas Mandala Waluya, 2026)
Sexually transmitted infections are increasing every year, and one group at risk of contracting STIs is adolescents. Lack of information about STIs leads to adolescents engaging in more deviant behavior, including casual sex, which puts them at risk of contracting STIs. This community service project aims to increase the knowledge of adolescents at Manado State Senior High School 7 through education on STIs prevention. The community service method includes lectures, accompanied by learning media such as laptops, LCDs, and leaflets, as well as Focus Group Discussions (FGDs) and a sound system. This community service was carried out on May 22-23, 2023, with 60 participants. The results of the community service activities carried out at SMA Negeri 7 Manado showed a significant increase in knowledge regarding Sexually Transmitted Infections in adolescents after being given health education with an average (mean) knowledge score before education of 59.13 to 94.83 after education, meaning there was a significant change in understanding of the material provided. This success is an important basis for promotive and preventive efforts to prevent the increase in STI cases among adolescents, especially in Manado City.